Synthesis and lipophilicity evaluation of some novel indole-containing pseudopeptides - Alavijeh, Nahid S.; Ramezanpour, Sorour; Alavijeh, Mohammad S.; Balalaie, Saeed; Rominger, Frank; Misra, Anil; Bijanzadeh, Hamid Reza (Monatshefte für Chemie, 2014)
An efficient synthesis of indole-containing pseudopeptides via an Ugi four-component reaction among indolecarboxylic acids, aromatic aldehydes, primary amines, and isocyanides in methanol is described. The lipophilicity of the synthesized compounds was determined using the n-octanol/PBS shake-flask procedure. The lipophilicity studies showed that most of the compounds possess the optimal range of lipophilicity for oral absorption, cell membrane penetration, and blood-brain barrier permeation.
Published online: 5 November 2013
Gesehen am 09.10.2020